Gastrodin Ameliorates Cognitive Dysfunction in Diabetes Rat Model via the Suppression of Endoplasmic Reticulum Stress and NLRP3 Inflammasome Activation - Ye, Tianyuan; Meng, Xiangbao; Zhai, Yadong; Xie, Weijie; Wang, Ruiying; Sun, Guibo; Sun, Xiaobo (Frontiers in Pharmacology, 2018)
Patients with diabetes mellitus (DM) are at high risk for cognitive dysfunction. Endoplasmic reticulum stress (ERS) and inflammation play crucial roles in DM. Gastrodin (Gas), the main component of Gastrodia elata, possesses anti-oxidative stress, anti-inflammatory, and neuroprotective effects. This present study aims to investigate whether Gas could ameliorate cognitive dysfunction in DM and to explore its underlying mechanisms. Rats with streptozotocin-induced type 2 DM were used in this study. After administration of Gas for 5 weeks, the levels of TC, TG, LDL-C and HDL-C in serum, TNF-α, IL-1β, MDA and SOD in the hippocampus were measured. Morris water maze, HE and Nissl staining were used to assess the effects of Gas on cognitive function and hippocampal neuronal apoptosis. Protein levels of GLUT3, BDNF, GRP78, PERK, P-PERK, TXNIP, ASC, NLRP3, CHOP, Bcl-2 and Bax were measured by using Western blot. The results showed that Gas could improve hyperglycemia and dyslipidemia in DM rats, as the levels of TC, TG LDL-C in serum were decreased. TNF-α, IL-1β, MDA contents in the hippocampus were decreased, and SOD contents was increased in the hippocamps of DM rats. Inflammation, oxidative stress, ERS, and apoptosis were observed in the hippocampus of DM rats, accompanied with decreased expression of BDNF and GLUT3. Gas improved the cognitive deficits caused by diabetes and inhibited inflammation, oxidative stress, ERS, and apoptosis in the hippocampus. Furthermore, Gas substantially increased the expression of GLUT3, and inhibited hippocampal ERS and ERS-mediated apoptosis. Additionally, Gas increased the expression of BDNF and decreased the activation of NLRP3 inflammasome. These results suggested that by inhibiting ERS and NLRP3 inflammasome activation and increasing the expression of BDNF and GLUT3, Gas exhibits neuroprotective effects against cognitive dysfunction in DM.